2021
DOI: 10.1093/jas/skab085
|View full text |Cite
|
Sign up to set email alerts
|

Determining the stability of accuracy of genomic estimated breeding values in future generations in commercial pig populations

Abstract: Genomic information has a limited dimensionality (Me) related to the effective population size. Under the additive model, the persistence of genomic accuracies over generations should be high when the nongenomic information (pedigree and phenotypes) is equivalent to Me animals with high accuracy. The objective of this study was to evaluate the decay in accuracy over time and to compare the magnitude of decay with varying quantities of data, and with traits of low and moderate heritability. The dataset included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In setting parents of the validation animals to missing, the relationship between genotyped and non-genotyped animals might become zero (i.e., A 12 = 0) and in such situation, H −1 will not contribute to the estimation of group effects ( Tsuruta et al, 2019 ). Truncation of the data set, e.g., only considering data after the year 2000, may also reduce the number of genetic groups, and has been found to reduce prediction biases ( Cesarani et al, 2021 ; Hidalgo et al, 2021 ; Hollifield et al, 2021 ; Macedo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In setting parents of the validation animals to missing, the relationship between genotyped and non-genotyped animals might become zero (i.e., A 12 = 0) and in such situation, H −1 will not contribute to the estimation of group effects ( Tsuruta et al, 2019 ). Truncation of the data set, e.g., only considering data after the year 2000, may also reduce the number of genetic groups, and has been found to reduce prediction biases ( Cesarani et al, 2021 ; Hidalgo et al, 2021 ; Hollifield et al, 2021 ; Macedo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For pigs, a higher heritability growth trait and a lower heritability fitness trait were examined. The initial heritability was 0.21 for the growth trait and 0.05 for the fitness trait (Hollifield et al 2021), and the calculated heritability was slightly higher (0.26) for the growth trait and almost the same (0.06) for the fitness trait.…”
Section: Heritability Calculationsmentioning
confidence: 89%
“…The formula for heritability was tested with data extracted from several studies, which included milk yield in Holsteins (Cesarani et al 2021), growth and fitness traits in pigs (Hollifield et al 2021), and a growth trait in broiler chicken (Hidalgo et al 2021). The information extracted included initial heritabilities used in the calculations, approximate number of genotyped animals with phenotypes in both reference and validation populations, and calculated accuracy or predictivity.…”
Section: Datamentioning
confidence: 99%
“…The lack of effect of genomic information on SBV prediction in the present study is confirmed by the high correlation between ESBV and GSBV and the high regression coefficient of GSBV on ESBV that we obtained. In our study, the small benefit from genomic information is likely due to the small number of available genotyped animals with accurate phenotype information, much smaller than the expected number (1690, [40]) that is necessary to represent the genomic structure of the population [41]. Consequently, too little of the genetic variance could be captured by the genomic information in this dataset to have a significant impact on ESBV.…”
Section: Pedigreementioning
confidence: 94%